Role of Trusting Beliefs and Trust in the Adoption of Online Reviews of Hotels : Extension of the IAM Model - Gautam, Shalini; Malik, Priyanka; Jain, Shanu (Indian Journal of Marketing, 2022)
This study examined the role of trusting beliefs (TB) and trust in online reviews of hotels. It proposed to extend the information adoption model (IAM) to describe the usefulness of online reviews. The other factors examined were source credibility (SC), relevance, and accuracy. The study’s conceptual model was tested on 208 respondents using structural equation modeling (SEM). The study investigated the precursors to information usefulness (IU), which was strongly associated with information adoption (IA). It revealed that trust in online reviews had a strong association with their IU, but there was no direct relationship between the SC of these reviews and IU. SC was associated with trust, which was associated with IU. TB was also strongly associated with SC. Relevance was associated with IU, but accuracy was not associated with the same. .